Functional determinants of lysophospholipid- and voltage-dependent regulation of TRPC5 channel - Ptakova, Alexandra; Zimova, Lucie; Barvik, Ivan; Bon, Robin S; Vlachova, Viktorie (Cellular and molecular life sciences : CMLS, 2024)
Lysophosphatidylcholine (LPC) is a bioactive lipid present at high concentrations in inflamed and injured tissues where it contributes to the initiation and maintenance of pain. One of its important molecular effectors is the transient receptor potential canonical 5 (TRPC5), but the explicit mechanism of the activation is unknown. Using electrophysiology, mutagenesis and molecular dynamics simulations, we show that LPC-induced activation of TRPC5 is modulated by xanthine ligands and depolarizing voltage, and involves conserved residues within the lateral fenestration of the pore domain. Replacement of W577 with alanine (W577A) rendered the channel insensitive to strong depolarizing voltage, but LPC still activated this mutant at highly depolarizing potentials. Substitution of G606 located directly opposite position 577 with tryptophan rescued the sensitivity of W577A to depolarization. Molecular simulations showed that depolarization widens the lower gate of the channel and this conformational change is prevented by the W577A mutation or removal of resident lipids. We propose a gating scheme in which depolarizing voltage and lipid-pore helix interactions act together to promote TRPC5 channel opening.
Keywords: mutace; Animals; Molecular Dynamics Simulation; membránové potenciály; HEK293 Cells; TRPC Cation Channels; lidé; lysofosfolipidy; simulace molekulární dynamiky; Mutation; kationtové kanály TRPC; Ion Channel Gating; Lysophospholipids; HEK293 buňky; gating iontového kanálu; Lysophosphatidylcholines; zvířata; lysofosfatidylcholiny; Membrane Potentials; Humans